Diagnosis and management of chronic persistent dry cough. - Chung, K. F. (BMJ Group, 1996)
Cough is one of the commonest symptoms of lung disease and is a frequent problem encountered in general practice as well as in hospital practice. A wide range of disease processes may present with cough and definitive treatment depends on making an accurate diagnosis of the cause. A diagnostic work-up for patients with persistent dry cough is presented. The most common associated conditions are post-viral cough, asthma, rhinosinusitis (post-nasal drip or 'nasal catarrh') and gastro-oesophageal reflux. Treatment with angiotensin-converting enzyme inhibitors can also lead to a persistent dry cough. Specific treatment of the cause should control the cough, but this may not occur in all cases and in a sizeable proportion of patients, no associated cause can be found. An increased sensitivity of the cough reflex can be observed in patients with persistent dry cough. Symptomatic relief must be considered when the cough interferes with the patient's health and sleep but the most effective antitussive opiates cause sedation and may be addictive. Treatment of persistent dry cough remains a challenge in some patients and there is still scope for improvement in its diagnosis and effective therapy.